Central imaging of pain - Flor, Herta; Bushnell, M. Catherine (The neurobiology of pain, 2005)
This chapter concentrates on the representation of pain in the human brain, covering relevant work from neuroelectric and neuromagnetic source imaging (ESI and MSI), functional magnetic resonance imaging (fMRI), magnetic resonance spectroscopy (MRS), positron emission (PET), and single photon emission computed tomography (SPECT) performed in healthy humans during acute pain, as well as studies performed in chronic pain sufferers. The focus is on the central imaging of pain in humans, although animal studies will be included when necessary. The chapter discusses persistent research questions and methodological developments related to imaging the central representation of pain in humans.
Gesehen am 11.11.2020